PROFIL PEMBIAYAAN PENDIDIKAN UNTUK MENINGKATKAN MUTU DAN PEMERATAAN PENDIDIKAN DASAR - Yoyon Suryono (Jurnal Kependidikan, 2003)
Abstract Education budget is assumed to have a strong relationship with quality improvement and opportunity equalization  especially at the basic education level. Therefore, it is necessary to identify an education-financial model that can improve uthe quality and accessibility of education. This research was an  evaluative type of survey, 36 Public Elementary Schools and 18 Private Elementary Schools were included, and 162 respondents were purposively selected to find out the profile of education budget at basic education level and then a model of education budget was explored. The results of this study indicated that most  of public  elementary schools revenue mostly came from the parents and community sources. The biggest portion of expenditure was allocated for teacher salary , and only a small portion was allocated for instrumental activities and for procurement of facilities. The direct and indirect cost paid the parents was bigger than in private schools, and most of which was the direct cost. The unit cost for private school was bigger. This study also found out that  there was relationship between the quality and accessibility  on the one side, and the revenue and expenditure compositions at the school level on the other side. Based on the result of this study, basic policies are needed to decrease the school dependency on government sources, and to increase the community sources for increasing the basic education quality and accessibility. The core polity problem is “ Who is responsible for which budget component” Keywords: education cost, education budget, education finance, quality and accessibility, basic education, school effectiveness